Hubungan Pola Konsumsi Makanan Kariogenik dan Non-Kariogenik dengan Pengalaman Sakit Gigi pada Siswa SMP Mojokerto - Sari, Meirna Dewita; Nerito, Prima (Bhakta Dental Journal, 2024)
Food consumption patterns (cariogenic and non-cariogenic) consumed in excess can cause toothache The purpose of this study was to determine the distribution of cariogenic and non-cariogenic food consumption patterns and their relationship with the experience of toothache in Mojokerto junior high school students. This study was a descriptive quantitative study with a cross sectional design conducted at Mojokerto Junior High School. The population was all Mojokerto junior high school students with a sample size of 178 students, obtained by purposive sampling technique. Analysis using Chi Square Test. It was found that the majority of respondents were female (56.7%) with the most age 13 years (61.2%). The prevalence of toothache with cariogenic food consumption patterns in Mojokerto junior high school students is high (76.9%). Chi Square test results stated that there was a significant relationship between cariogenic food consumption patterns and toothache experience in Mojokerto junior high school students with a P value of 0.041 (<0.05 = α value). There is a significant relationship between cariogenic food consumption patterns and toothache experience in Mojokerto junior high school students. It is expected that the school can identify the impact of cariogenic food consumption, so as to reduce the sale of cariogenic foods in the school environment.